Fixed and common fixed point theorems in frame of quasi metric spaces under contraction condition based on ultra distance functions - Shatanawi, Wasfi (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we introduce the notion of ultra distance function. Based on the notion of ultra distance function, we introduce the definitions of (k, ψ, L)-quasi contractions of type (I) and type (II) in the frame of quasi metric spaces. We employ our new definitions to construct and prove many fixed and common fixed point results in the frame of quasi metric spaces. Our results extend and improve many exciting results in the literatures. Also, we introduce some examples and some applications in order to support the usability of our work.
Keywords: quasi metric spaces; fixed-point theorems; nonlinear contractions; comparison functions; almost perfect mappings